1994
DOI: 10.1007/bf00863777
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial haematomas following bone marrow transplantation

Abstract: Intracranial haemorrhage (ICH) is a known grave complication of leukaemia and has been described post mortem following bone marrow transplantation (BMT). Ante mortem following BMT, the incidence and significance of ICH is not well defined. The records of 471 bone marrow transplantation recipients over 11 years at the Hadassah University Hospital Bone Marrow Transplantation Department were reviewed. The relevant data of all patients with ICH were analysed. A resolute diagnostic and treatment protocol for subdur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Sixteen (51.6%) of these 31 cases were CNS hemorrhage, and thus 8.8% of patients (16/180) who died after BMT and underwent an autopsy had CNS hemorrhage as the main cause of death. Although Pomeranz et al 12 concluded that ICH is uncommon following BMT, these authors observed a high mortality rate among patients with ICH following BMT.…”
Section: Discussionmentioning
confidence: 95%
“…Sixteen (51.6%) of these 31 cases were CNS hemorrhage, and thus 8.8% of patients (16/180) who died after BMT and underwent an autopsy had CNS hemorrhage as the main cause of death. Although Pomeranz et al 12 concluded that ICH is uncommon following BMT, these authors observed a high mortality rate among patients with ICH following BMT.…”
Section: Discussionmentioning
confidence: 95%
“…1 This may be due to several factors, such as malignancy, thrombocytopenia, heparin treatment and intrathecal treatment. It is difficult to say which risk factors are of importance, because SDH is a rare event.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are more common in patients with leukaemia and after haematopoietic stem cell transplantation (HSCT). 1 The reported incidences of SDH vary depending on the diagnosis and treatment. [2][3][4] Post-puncture headache has been said to be caused by cerebrospinal fluid leakage, followed by decreased intracranial pressure, leading to traction of pain-sensitive vessels that also may rupture.…”
mentioning
confidence: 99%
“…Other reports associated intracranial hemorrhage with thrombocytopenia. 19,20 It is possible that rare, but serious complications are more common with low platelet counts. In our study, samples of both pulmonary and intracranial hemorrhage (on the first bleeding day) were small.…”
Section: Tablementioning
confidence: 99%
“…In 24 patients who bled they identified 'high platelet consumption factors' (eg disseminated intravascular coagulation, fever, sepsis, veno-occlusive disease of the liver, mucositis) as associated risk factors for bleeding. Thrombocytopenia was significantly associated with intracranial hemorrhage after BMT, 19,20 but many reports on bleeding from other sites (gastrointestinal hemorrhage, hemorrhagic cystitis, pulmonary hemorrhage) have not identified thrombocytopenia as a main cause of bleeding, implicating other etiologies (eg preparative regimen toxicity, infections, graft-vs-host disease). [21][22][23][24][25][26][27][28][29][30][31][32] We have previously studied 1402 patients for bleeding complications within 100 days after BMT.…”
mentioning
confidence: 99%